Coronary artery remodelling is related to plaque composition. Issue 3 (17th June 2005) - Rodriguez-Granillo, G A; Serruys, P W; Garcia-Garcia, H M; Aoki, J; Valgimigli, M; van Mieghem, C A G; McFadden, E; de Jaegere, P P T; de Feyter, P
Abstract : Objective: To assess the potential relation between plaque composition and vascular remodelling by using spectral analysis of intravascular ultrasound (IVUS) radiofrequency data. Methods and results: 41 coronary vessels with non-significant (< 50% diameter stenosis by angiography), ⩽ 20 mm, non-ostial lesions located in non-culprit vessels underwent IVUS interrogation. IVUS radiofrequency data obtained with a 30 MHz catheter, were analysed with IVUS virtual histology software. A remodelling index (RI) was calculated and divided into three groups. Lesions with RI ⩾ 1.05 were considered to have positive remodelling and lesions with RI ⩽ 0.95 were considered to have negative remodelling. Lesions with RI ⩾ 1.05 had a significantly larger lipid core than lesions with RI 0.96–1.04 and RI ⩽ 0.95 (22.1 (6.3) v 15.1 (7.6) v 6.6 (6.9), p < 0.0001). A positive correlation between lipid core and RI ( r  =  0.83, p < 0.0001) and an inverse correlation between fibrous tissue and RI ( r  =  −0.45, p  =  0.003) were also significant. All of the positively remodelled lesions were thin cap fibroatheroma or fibroatheromatous lesions, whereas negatively remodelled lesions had a more stable phenotype, with 64% having pathological intimal thickening, 29% being fibrocalcific lesions, and only 7% fibroatheromatous lesions (p < 0.0001). Conclusions: In this study, in vivo plaque composition and morphology assessed by spectral analysis of IVUS radiofrequency data were related to coronary artery remodelling.